Exploring the J ratio of a diamond spin chain, in relation to phase transition - You, Liming (2019)
In this report, the experimentalist will be utilizing the method of exact diagonalization on the Hamiltonian matrix of the 1-dimensional, diamond spin-half chain model (which shall be abbreviated as DSC for the rest of this script for the purpose of brevity), where the interaction between the spins in the chain is solely Heisenberg, in order to determine the DSC’s ground state. As a caveat, all spin sites in this report will be half spins. The nature of the interaction between the different sites in this DSC shall be strictly Heisenberg, characterized by S​n​ ᆞS (n+1) for interaction between sites n and n+1. By varying the values of the coupling coefficients j1 and j2 which accounts for the structure for the DSC, and comparing the results to the extreme cases where the value of j1 greatly exceeds j2 (and vice versa), we will be able to obtain certain insights on the overall structure of the DSC